Kontekstualisasi Makna Ukhuwwah Islâmîyah perspektif Jemaah Tarekat Shatarîyah di Nganjuk Jawa Timur - Warsito, Warsito (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This article discusses the symbols, process, and meaning of ukhuwwah islâmîyah (Islamic brotherhood) within perspective of the followers of the Tarekat Shatârîyah in Tanjunganom Nganjuk East Java. The result of the research indicates that the making process of ukhuwwah islâmîyah has been initiated through bay?ah towards murshid (Guru Wasîtah). To the followers of the Tarekat Shatarîyah, murshid is a person who becomes the main symbol that unites them. Intensity of interaction and meetings have also played significant role in the creation process of ukhuwwah islâmîyah among the adherents the Tarekat. When they gather, they perform a number of rituals such as performing qiyâm al-layl and dhikr and reciting what so-called muji wali kutub. They also discuss various problems of religious and social issues. The making process of ukhuwwah islâmîyah is also convoyed with the use and carrying out of certain symbol and ritual such as wearing the Malakîyah ring and reciting Asmâ? 9. To the followers of this Tarekat, ukhuwwah islâmîyah means a brotherhood which is founded merely on the spirit of pure intention without any inclination to gain worldly benefits. To them it is a relation which is established on the basis of obedience upon Guru Wasîtah in order to create an eternal brotherhood for the sake of God regardless of their social status.